MODERN TECHNOLOGIES OF TEACHING TO READ TEXTS IN ENGLISH (Journal of Universal Science Research, 2025)
This article explores the role of digital reading platforms, artificial intelligence (AI)-driven applications, gamification, and adaptive learning systems in enhancing reading instruction. Additionally, it discusses the impact of these technologies on student performance, highlighting both the advantages and challenges of integrating them into educational settings.